Values and Participation : Development in Rural Indonesia - Budijanto, Bambang (Book collections on Project MUSE., 2009)
Socio-religious values and socioeconomic development are interdependent, interrelated, and constantly changing in the context of macro political structures, economic policy, religious organizations, and globalization, as well as in the context of micro influences such as local affinities, identity, politics, leadership, and beliefs. The three Lopait communities in Central Java, Indonesia, provide an excellent model of rich and complex negotiations and interactions among all of the factors named above. This book argues that the comprehensive approach to understanding the socio-religious values of each local community is essential in order to accurately describe their respective identities, which will help institutions and agencies, both governmental and nongovernmental, to relate to these communities with dignity and respect.